A generalized, ordinary, finite deformation constitutive correspondence model for peridynamics. (1st June 2018) - Foster, John T.; Xu, Xiao
Abstract: A finite deformation constitutive framework for peridynamics that uses generalized Kirchhoff stress measures as intermediate quantities in computing the peridynamic material point interactions is proposed. It is shown to be a generalization of a previous finite deformation constitutive correspondence theory and has additional useful properties. The new model is shown to be an ordinary material model and therefore conserves angular momentum without additional restrictions. Additionally, it does not suffer from well-known "surface effects" present in some peridynamic material models, has improved material stability properties, and allows for inclusion of elasto-plastic behavior in a straightforward manner.